The impact of COVID-19 on populations living at high altitude: Role of hypoxia-inducible factors (HIFs) signaling pathway in SARS-CoV-2 infection and replication - Devaux, Christian Albert; Raoult, Didier (Frontiers in Physiology, 2022)
Cases of coronavirus disease 2019 (COVID-19) have been reported worldwide. However, one epidemiological report has claimed a lower incidence of the disease in people living at high altitude (>2,500 m), proposing the hypothesis that adaptation to hypoxia may prove to be advantageous with respect to SARS-CoV-2 infection. This publication was initially greeted with skepticism, because social, genetic, or environmental parametric variables could underlie a difference in susceptibility to the virus for people living in chronic hypobaric hypoxia atmospheres. Moreover, in some patients positive for SARS-CoV-2, early post-infection 'happy hypoxia" requires immediate ventilation, since it is associated with poor clinical outcome. If, however, we accept to consider the hypothesis according to which the adaptation to hypoxia may prove to be advantageous with respect to SARS-CoV-2 infection, identification of the molecular rational behind it is needed. Among several possibilities, HIF-1 regulation appears to be a molecular hub from which different signaling pathways linking hypoxia and COVID-19 are controlled. Interestingly, HIF-1 was reported to inhibit the infection of lung cells by SARS-CoV-2 by reducing ACE2 viral receptor expression. Moreover, an association of the rs11549465 variant of HIF-1α with COVID 19 susceptibility was recently discovered. Finally, curcumin reported as being beneficial for COVID-19 patients, inhibits SARS-CoV-2 binding to target cells and inactivates the functional transcription complex HIF-1α,-CBP/p300. Here, we review the evidence for a link between HIF-1α, ACE2 and AT1R expression, and the incidence/severity of COVID-19. We highlight the central role played by the HIF-1α signaling pathway in the pathophysiology of COVID-19.